Hepatitis C-Associated Mixed Cryoglobulinemic Vasculitis Induces Differential Gene Expression in Peripheral Mononuclear Cells - Sidharthan, Sreetha; Kim, Cheol-Woo; Murphy, Alison A.; Zhang, Xiaozhen; Yang, Jun; Lempicki, Richard A.; Sneller, Michael C.; Kottilil, Shyam (Frontiers in Immunology, 2014)
This study examines the distinct gene expression profile of peripheral blood mononuclear cells from patients with chronic hepatitis C (CHC) infection and mixed cryoglobulinemic (MC) vasculitis. Our DNA microarray analysis indicates that HCV-associated MC vasculitis is characterized by compromised neutrophil function, impaired chemotaxis, and increased interferon stimulated gene (ISG) expression, contributing to overall MC pathogenesis and end organ damage. Increased ISG expression is suggestive of an enhanced endogenous interferon gene signature. PBMC depletion assays demonstrate that this increased expression is due to an activation of monocytes and not a direct result of B cell expansion. Notably, this monocyte activation of ISG expression in HCV-associated MC vasculitis suggests a poor predictor status of interferon-based treatment. Further analysis of PBMC gene expression profiles before and after in vivo B cell depletion therapy is critical to completely understanding the mechanisms of MC vasculitis pathogenesis.